Transgenerational impact of climatic changes on cotton production - Farooq, Muhammad Awais; Chattha, Waqas Shafqat; Shafique, Muhammad Sohaib; Karamat, Umer; Tabusam, Javaria; Zulfiqar, Sumer; Shakeel, Amir (Frontiers in Plant Science, 2023)
Changing climatic conditions are an increasing threat to cotton production worldwide. There is a need to develop multiple stress tolerant cotton germplasm which can adapt to wide range of environments. For this purpose, 30 cotton genotypes were evaluated for two years under drought (D), heat (H), and drought+heat stresses (DH) under field conditions. Results indicated that plant height, number of bolls, boll weight, seed cotton yield, fiber fineness, fiber strength, fiber length, K+, K+/Na+, relative water contents (RWC), chlorophyll a and b, carotenoids, total soluble proteins got reduced under D, H and were lowest under DH whereas, superoxidase dismutase (SOD), H2O2, Na+, GOT%, total phenolic contents, ascorbate, and flavonoids got increased for consecutive years. Correlation studies indicated that there was a positive correlation of most of the traits with one another but a negative correlation with H2O2, and Na+ ions. PCA and clustering analysis indicated that MNH-786, KAHKSHAN, CEMB-33, MS-71, FH-142, NIAB-820, CRS-2007, and FH-312 performed consistently better than other genotypes for most traits under stress conditions. Identified genotypes can be utilized in the future cotton breeding program to develop high-yielding climate change-resilient cotton.